Laser additive complex inner cavity structure support removing and inner wall finishing method

By matching the design interface feature recognition with the additive manufacturing process in the laser powder bed melting LPBF technology, and combining electrochemical post-processing, the removal of the support structure of complex inner cavity structure and the finishing processing of the inner wall is achieved, and the existing technology is solved The problem of difficulty in removing the middle inner cavity support structure and low inner wall forming quality has been obtained, and the effect of efficient complex inner cavity structure forming is achieved.

CN119457118AActive Publication Date: 2025-02-18NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411466612.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-18
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

When forming complex inner cavity/inner runner structures, laser powder bed molten LPBF technology faces difficulties in removing inner cavity support structures and low inner wall forming quality. The existing methods cannot synchronize the removal of support structures and the finishing of inner walls.

Method used

A method of supporting removal of complex inner cavity structures of laser additives and finishing the inner wall, including selecting matrix materials with precipitation reinforcement characteristics and good melt forming properties of laser powder beds, design interface feature recognition and division, and performing differentiated additive manufacturing Laser process matching, combined with electrochemical post-treatment to achieve the removal of support structures and the finishing of inner walls.

Benefits of technology

It realizes efficient removal of the internal support structure of complex inner cavity structure and finishing the inner wall, solves the problems of "step effect" and slag-mounted powder, and obtains a smooth and unsupported laser additive manufacturing complex inner cavity structure, which broadens the The application of this technology in the field of aerospace.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119457118A_ABST
    Figure CN119457118A_ABST
Patent Text Reader

Abstract

The invention discloses a method for removing a support of a complex inner cavity structure and finishing an inner wall of the complex inner cavity structure through laser additive manufacturing, aims to solve the problems of removing the support structure of a complex inner cavity component and finishing the inner wall of the complex inner cavity component in the existing laser additive manufacturing, and aims at precipitation strengthening alloy systems such as aluminum alloy and nickel-based high-temperature alloy. According to the method, the rich precipitation corrosion weakening layer is preset by increasing laser energy input in the inner cavity / support interface, controllable dissolution and support removal of the entity / support interface are completed in combination with the electrochemical post-treatment process, and the step effect and slag adhering and powder adhering finishing in the wall face of the complex inner cavity are synchronously achieved; and a smooth and unsupported laser additive manufacturing complex inner cavity structure is obtained. According to the method, the problems that an auxiliary support of an existing laser additive manufacturing complex inner cavity structure cannot be removed, and finishing of the inner cavity is difficult are synchronously solved, the application range of the laser additive manufacturing complex inner cavity structure is widened, and operability is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of additive manufacturing, and in particular relates to a method for removing supports of a complex inner cavity structure and finishing an inner wall by laser additive manufacturing. Background Art

[0002] Laser additive manufacturing technology can realize the integrated forming of complex components based on the layer-by-layer melting and deposition process. In particular, the laser powder bed fusion technology (LPBF) based on the powder bed laying process can realize the layer-by-layer powder laying and laser selective melting and deposition process with a layer thickness of micrometer level (20-50 μm), which is very advantageous in the field of forming precision and complex parts in the aerospace field. However, the current LPBF technology still faces forming constraints. In the process of forming overhanging feature structures, the high-energy laser beam directly acts on the loose powder bed, which is easy to form slag at the bottom of the overhanging structure and local heat accumulation warping, resulting in a significant reduction in dimensional accuracy and surface finish. Therefore, for the forming of complex structure overhanging surfaces, it is usually necessary to design an auxiliary support structure between the forming substrate and the overhanging surface to suppress slag sticking, stabilize the forming process and resist stress deformation. The support structure is crucial for LPBF forming complex structures. However, at present, there are still two technical difficulties in the process of LPBF forming with complex inner cavity / inner flow channel structures.

[0003] First, the auxiliary support structure needs to be removed after forming. At present, the post-processing removal of LPBF auxiliary support structure is usually achieved by cutting and auxiliary bench grinding. However, for components with complex inner cavity structures, the internal overhanging surface needs to add support structure during the forming process to ensure the forming quality. After forming, it cannot be cut due to the limitation of three-dimensional space size. Therefore, the post-processing removal method of the internal auxiliary support structure of LPBF forming complex inner cavity structure is one of the key process technology problems that need to be solved at present. Second, the layer-by-layer and channel-by-channel forming characteristics of LPBF are prone to produce a "step effect" in the formation of complex inner cavity structures with curvature, resulting in a significant reduction in surface quality. At the same time, complex inner cavities are prone to form inner wall sticking powder and hanging slag during the forming process, which affects the service characteristics of complex flow channels, so it is necessary to perform the inner wall finishing processing of the flow channel. At present, the commonly used inner flow channel finishing processing methods include abrasive flow, chemical polishing, electrochemical polishing, etc., but they are not very applicable to additive manufacturing of complex structures, fine diameters, large-angle inner flow channels, etc., and the support structure cannot be removed.

[0004] In summary, LPBF technology has great advantages in the field of forming complex aerospace structural parts, but it still faces the problems of difficulty in removing the inner cavity support structure and low inner wall forming quality in the forming of complex inner cavity / inner flow channel structures. At present, there is no process method to simultaneously achieve the removal of the inner cavity support structure and the finishing of the inner wall. Summary of the invention

[0005] Purpose of the invention: The technical problem to be solved by the present invention is to solve the problem of difficulty in removing the inner cavity support structure and low inner wall forming quality in the existing laser powder bed melting (LPBF) technology for forming a complex inner cavity / inner flow channel structure, and propose a method for removing the inner cavity support structure and finishing the inner wall.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for removing support of a complex inner cavity structure and finishing the inner wall by laser additive manufacturing comprises the following steps: S1. Selection of suitable matrix materials: Select matrix materials with precipitation strengthening characteristics and good laser powder bed melting formability, including any one of lightweight high-strength aluminum alloy and nickel-based high-temperature alloy; S2. Interface feature identification: Use support adding software to design and add supports for components with complex inner cavity structures, identify and divide interface features in the contact area between the inner cavity support and the component entity, and divide it into "solid material area", "weakened interface area" and "support structure area" from top to bottom; S3, laser additive manufacturing process matching: performing differentiated additive manufacturing laser process matching on the interface feature area of ​​step S2, and using the laser energy density method to measure its laser energy input; The laser energy density in the “solid material area” is η 实 , the laser energy density in the “weakened interface region” is η 界 , the laser energy density in the “support structure area” is η 支 ;in, η 界 / η 实 ≥1.5, and η 支 / η 实 ≤0.8; S4. Electrochemical post-treatment: The above-formed additive component is connected to the anode as a working electrode, and the titanium mesh is connected to the cathode as a counter electrode, and is placed in a corrosion tank containing a polishing liquid and subjected to electrochemical post-treatment.

[0007] Preferably, in step S1, the lightweight and high-strength aluminum alloy includes but is not limited to Al-Cu alloy (Cu 4.0-5.5wt%), Al-Mg-Si alloy (Si 4.0-7.0 wt%, Mg 0.1-1.0 wt%), Al-Zn alloy (Zn 2.0-8.0 wt%, Mg0.1-3.0 wt%), trace element modified Al-Mg alloy, trace element modified Al-Mn alloy, etc.

[0008] Preferably, the trace elements include but are not limited to Sc, Zr, Er, Ti and the like.

[0009] Preferably, in step S1, the nickel-based high-temperature alloy includes but is not limited to GH4169 alloy, Inconel 600 alloy, Inconel 625 alloy, Rene 80 alloy, Rene 125 alloy, Rene 142 alloy, etc.

[0010] Specifically, in step S2, the overhanging surface is identified according to the base alloy, wherein the angle between the aluminum alloy and the substrate is ≤45°, and the angle between the nickel-based alloy and the substrate is ≤35°, and self-use supports are added to the marked overhanging surface, and the support types include but are not limited to block supports, conical supports, mixed supports, etc.

[0011] Specifically, in step S2, the bottom boundary of the "solid material area" coincides with the model contour; the thickness of the "weakened interface area" is between 0.5 mm and 1 mm, and its top interface coincides with the model contour; the top area of ​​the "support structure area" coincides with the bottom of the "weakened interface area".

[0012] Specifically, in step S3, the laser energy density of each interface characteristic region is calculated by the formula η = P / V D is determined; where the laser power is defined as P , unit W, the suitable range is 200-150 W; the laser scanning speed is defined as V , unit: mm / s, suitable range: 800 mm / s-2500 mm / s; scanning interval is defined as h , unit μm, the suitable range is 60-120μm; the scanning layer thickness is defined as d, The unit is μm, and the suitable range is 30-50μm.

[0013] Preferably, in step S4, the electrolyte concentration of the electrochemical post-treatment is 0.5-1.0 mol / L, the treatment temperature is 35° C., the treatment time is 0.5-5 h, and the voltage is 6-10 V.

[0014] Preferably, in step S4, for the aluminum alloy matrix material, the electrolyte may be: Na2CO380-120g / L, Na3PO445-75g / L, NaOH 1540g / L, complexing agent 15-40mL / L, solvent is water; tank temperature 5080°C, current density 520A / dm 2 , voltage 2-4V, time 15 min -4 h.

[0015] Preferably, in step S4, for the nickel-based alloy matrix material, the electrolyte can be a mixed aqueous solution of 60-80% phosphoric acid and 20-40% sulfuric acid, the bath temperature is 4070°C, and the current density is 4060A / dm 2 , voltage 2-4 V, time 1 min -30 min. Beneficial Effects

[0016] The present invention takes additive manufacturing as the object to form a complex inner cavity component support structure and inner surface finishing collaborative processing, designs a 0.5-1 mm thick weakened layer at the interface between the component entity and the support structure, and combines the laser process to adjust the energy input of the weakened layer at the interface to η 界 / η 实 ≥1.5, for precipitation-strengthened alloy systems, the weak interface designed for complex inner cavity entities / supports is controlled to coarsen due to increased energy input. In the interface weakening zone, due to the increase in laser energy, the heat accumulation effect of the molten pool increases, resulting in a slowdown in the solidification rate due to temperature increase, which in turn promotes the enrichment and coarsening of Al3 (Sc, Zr) precipitates along the grain boundaries. These enriched and coarsened precipitates distributed along the weakened zone have a significant potential difference with the matrix, and local micro-galvanic couples are formed and rapidly dissolved in the subsequent electrochemical polishing process. Through the controllable corrosion and dissolution of the weakened interface layer along the preset weakened layer due to precipitation coarsening during the polishing process, the internal support structure of the complex inner cavity structure is removed by post-processing, and the "step effect" and slag and powder finishing processing of the complex inner cavity wall are simultaneously realized, so as to obtain a smooth and support-free laser additive manufacturing complex inner cavity structure. This method simultaneously solves the current problems of the inability to remove the auxiliary support of the complex inner cavity structure in laser additive manufacturing and the difficulty of inner cavity finishing processing, broadens the application of laser additive manufacturing of complex inner cavity structures, and has strong operability. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0018] Figure 1 It is a process flow chart of the method of the present invention.

[0019] Figure 2 Schematic diagram of the support / solid interface feature recognition process for additive manufacturing of complex internal cavity structures.

[0020] Figure 3 This is a microstructure diagram of the interface weakened layer after matching the additive process proposed in the present invention.

[0021] Figure 4 It is a surface SEM image of Example 1 in a specific implementation manner.

[0022] Figure 5 It is a surface SEM image of Example 3 in the specific implementation manner.

[0023] Figure 6 It is a surface SEM image of Example 6 in the specific implementation manner.

[0024] Figure 7 It is a surface SEM image of Example 8 in a specific implementation manner. DETAILED DESCRIPTION

[0025] The present invention can be better understood with reference to the following examples. Example 1

[0026] Combination Figure 1 The method for removing support and finishing the inner wall of a complex inner cavity structure by laser additive manufacturing of the present invention comprises the following steps: Step 1: Prefer an alloy system with precipitation strengthening characteristics and good laser powder bed melt formability. The selected material system is Al-Mg-Mn-Si alloy, where the alloy components are Mg 7-9 wt.%, Si 0.4-1.2 wt.%, Mn 0.3-0.8 wt.%, Sc 0.5-0.7 wt.%, Zr 0.2-0.5 wt.%, and the balance is Al. The original material is spherical alloy powder with a powder particle size of 15-53 μm and D 50 ≥23 μm. The powder should be dry and have good flowability.

[0027] Step 2: For the parts with complex inner cavity structures to be formed, first use pre-processing software such as Materialslise Magics to add supports, identify the overhanging surface according to the original alloy system, where the angle between the aluminum alloy and the substrate is ≤45° (the angle between the nickel-based alloy and the substrate is ≤35°). Add self-use supports on the marked overhanging surface, and the support types include but are not limited to block supports, conical supports, and mixed supports. Furthermore, select the support structure generated in the inner cavity of the complex component, and identify and divide the feature area at the support / solid component interface.

[0028] The feature interface recognition and division process is as follows Figure 2 As shown in the figure, for the contact part between the complex inner cavity support structure and the solid part, from top to bottom, they are "solid material area", "weakened interface area" and "support structure area". The bottom boundary of the solid material area coincides with the model contour. The thickness of the weakened interface area should be between 0.5 mm and 1 mm, and its top interface coincides with the model contour. The top area of ​​the support structure area coincides with the bottom of the weakened interface area.

[0029] Step 3: After adding the support structure and identifying the feature interface in step 2, the additive process matching design is performed. First, the laser process range is determined for the "solid material area" using process tests. The laser energy density method is used to measure the laser energy input, where the laser power is defined as P , the laser scanning speed is defined as V , the scanning interval is defined as h , the scanning slice thickness is defined as d , then the laser energy density can be defined as: η = P / V D .

[0030] In the additive process matching process described in step 3, the ratio of the laser energy density in the weakened interface area to the laser energy density in the solid material area should satisfy η 界 / η 实 ≥1.5, the ratio of laser energy density in the support structure area to the laser energy density in the solid material area should meet η 支 / η 实 ≤0.8. Specifically, the fixed layer thickness is 30 μm, the scanning interval is 60 μm, the laser power in the solid material area is 350 W, and the laser scanning speed is 1200 mm / s; the laser power in the weakened interface area is 400 W, and the laser scanning speed is 800 mm / s; the laser power in the support structure area is 300 W, and the laser scanning speed is 1400 mm / s. Based on this process setting, standardized laser additive manufacturing is performed layer by layer until the processing is completed and the time is taken out to remove the powder in the inner cavity.

[0031] Step 4: Electrochemical post-treatment: Connect the complex inner cavity component formed by the above process to the anode as the working electrode, and connect the titanium mesh to the cathode as the counter electrode, and place it in the electrolyte corrosion tank for electrochemical post-treatment. The electrolyte tank temperature is 50-80℃, and the current density is 5-20A / dm 2 , voltage 2-4 V, time 1 h. Polishing temperature 35℃, polishing time 40-60 min, voltage 6-8 V. Based on the above steps, laser additive manufacturing of components with complex inner cavity structures, removal of inner cavity supports and finishing of inner cavity surfaces are achieved.

[0032] The electrolyte in step 4 is Na2CO3 80-120 g / L, Na3PO4 45-75 g / L, NaOH 15-40 g / L, and complexing agent 15-40 mL / L.

[0033] Figure 3 This is the microstructure diagram of the interface weakening layer after the additive process matching of the present invention. Figure 4This is a SEM image of the surface of the component formed in this embodiment. It can be seen that in the interface weakening zone, due to the increase in laser energy, the heat accumulation effect of the molten pool increases, resulting in a slowdown in the solidification rate due to the temperature increase, which in turn promotes the enrichment and coarsening of Al3 (Sc, Zr) precipitates along the grain boundaries. These enriched and coarsened precipitates distributed along the weakening zone have a significant potential difference with the matrix, and local micro-galvanic couples are formed and rapidly dissolved in the subsequent electrochemical polishing process. By weakening the interface layer due to precipitation coarsening during the polishing process, controllable corrosion dissolution occurs along the preset weakening layer (such as Figure 4 As shown in the figure, the post-processing removal of the internal support structure of the complex inner cavity structure is realized, and the "step effect" inside the complex inner cavity wall and the slag and powder finishing processing are simultaneously realized to obtain a smooth and support-free laser additive manufacturing complex inner cavity structure. Example 2

[0034] The present embodiment is different from embodiment 1 in that the alloy system described in step one is a nickel-based high-temperature alloy, and the specific grade is GH416 alloy. In step two, the overhanging surface is identified as a nickel-based alloy with an angle of ≤35° with the substrate. The forming parameters in step three are specific, with a fixed layer thickness of 50 μm and a scanning interval of 60 μm. The laser power in the solid material area is 300 W, and the laser scanning speed is 1500 mm / s; the laser power in the weakened interface area is 400 W, and the laser scanning speed is 1000 mm / s; the laser power in the support structure area is 200 W, and the laser scanning speed is 1500 mm / s. In step four, the electrolyte is a mixture of 60-80% phosphoric acid and 20-40% sulfuric acid, the bath temperature is 40-70°C, and the current density is 40-60A / dm 2 , voltage 2-4 V, time 1 min -30 min. Others are the same as in Example 1. Example 3

[0035] The difference between this embodiment and embodiment 1 is that feature interface identification is not performed in step 2, and additive process matching design is not performed in step 3. All forming process parameters are fixed layer thickness of 30 μm, scanning spacing of 60 μm, laser power of 350 W, and laser scanning speed of 1200 mm / s. Other parameters are the same as those in embodiment 1. The surface SEM image of the component formed in this embodiment is shown in FIG. Figure 5 shown. Example 4

[0036] The difference between this embodiment and embodiment 1 is that in step 3, when designing the additive process matching, the energy density of the "weakened interface area" is reduced. Specifically, the laser power is 400 W and the laser scanning speed is 1000 mm / s. η 界 / η 实 =1.37<1.5. Others are the same as in Example 1. Example 5

[0037] The difference between this embodiment and the first embodiment is that in step 2, when the interface is identified and divided, the thickness of the "weakened interface area" is set to 0.3 mm. The rest is the same as the first embodiment. Example 6

[0038] The difference between this embodiment and embodiment 1 is that in step 2, when the interface is identified and divided, the thickness of the "weakened interface zone" is set to 1.5 mm. The rest is the same as embodiment 1. The surface SEM image of the component formed in this embodiment is as follows: Figure 6 shown. Example 7

[0039] The difference between this embodiment and embodiment 1 is that in step 2, the electrochemical post-treatment, the treatment time is set to 10 minutes. The rest is the same as embodiment 1. Example 8

[0040] The difference between this embodiment and embodiment 1 is that in step 2, the treatment time is set to 6 h. The rest is the same as embodiment 1. The surface SEM image of the component formed in this embodiment is as follows: Figure 7 shown.

[0041] The inner cavity section of the formed specimen was cut, ground and polished to observe the support removal and measure the inner wall roughness. The test results of different embodiments are shown in Table 1.

[0042] Table 1 Support removal effect and inner cavity surface roughness processed by different embodiments

[0043] From Table 1 we can see that: Comparison of Example 1 with Example 2 shows that this method has a good effect on aluminum alloys, nickel-based alloys and other systems with precipitation strengthening characteristics. Figure 4 As shown, the surface treated by this method is smooth and continuous, without obvious support structure residue and surface slag / powder sticking phenomenon, and the roughness is better than 1.6μm, achieving good post-processing surface finishing and support synchronous removal effect.

[0044] Comparing Example 1 with Example 3, when the key steps proposed by the present invention such as feature interface identification and additive process matching are missing, conventional methods cannot simultaneously achieve the removal of the inner cavity support structure and the inner wall finishing process. Figure 4 , the feature interface identification in step 2 and the additive process matching in step 3 proposed by the present invention were not applied during the processing. After the same electrochemical polishing treatment, the support structure still existed, that is, the support structure removal could not be achieved. At the same time, since the support structure was not removed, although the surface obtained a certain degree of finishing effect, the surface still had powder sticking phenomenon.

[0045] Comparing Example 1 with Example 4, when the laser energy density of the weakened interface layer is insufficient η 界 / η 实 =1.37<1.5. At this time, the coarsening degree of the weakened layer precipitate is not significantly different from that of the matrix material, and controllable dissolution and support removal along the interface layer cannot be achieved.

[0046] Comparing Example 1 with Example 5, when the thickness of the weakened interface layer is insufficient, the local energy is insufficient to produce a continuous coarsening and corrosion weakened layer, and controllable removal of the support structure cannot be achieved at this time.

[0047] Comparing Example 1 with Example 6, when the thickness of the weakened interface layer is too thick, Figure 4 With attached Figure 6 When the weakened interface layer proposed by this method is too thick, the remaining root after the support is removed causes large roughness. At the same time, the support structure is not completely removed, and it is impossible to achieve simultaneous support structure removal and surface finishing.

[0048] Comparing Example 1 with Example 7, when the electrochemical post-treatment time is too short, the controllable dissolution time of the weakened interface layer is insufficient, and the effect of post-treatment removal of complex inner cavity support cannot be achieved.

[0049] Comparative Example 1 and Example 8, Comparative Example 1 and Example 8 Figure 4 With attached Figure 7 When the electrochemical post-treatment time is too long, dissolution and corrosion pits appear in some of the inner cavity substrates. This is because the electrochemical treatment time is too long, a small amount of precipitated phase in the substrate reacts with the electrolyte to form local micro-galvanic couples, and the substrate material dissolves along the grain boundaries under long-term treatment, resulting in corrosion pits in the substrate and increased surface roughness.

[0050] The present invention provides a method and idea for removing the support of a complex inner cavity structure and finishing the inner wall by laser additive. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A method for removing support and finishing the inner wall of a complex inner cavity structure by laser additive manufacturing, characterized in that: The steps include: S1. Selection of suitable matrix materials: Select a matrix material with precipitation strengthening characteristics and good laser powder bed melting formability, including any one of aluminum alloy and nickel-based alloy; S2. Interface feature identification: Use support adding software to design and add supports for components with complex inner cavity structures, identify and divide interface features in the contact area between the inner cavity support and the component entity, and divide it into "solid material area", "weakened interface area" and "support structure area" from top to bottom; S3, laser additive manufacturing process matching: performing differentiated additive manufacturing laser process matching on the interface feature area of ​​step S2, and using the laser energy density method to measure its laser energy input; The laser energy density in the "solid material area" is η 实 , the laser energy density in the "weakened interface zone" is η 界 , the laser energy density in the "support structure area" is η 支 ; in, η 界 / η 实 ≥1.5, and η 支 / η 实 ≤0.8; S4. Electrochemical post-treatment: The above-formed additive component is connected to the anode as a working electrode, and the titanium mesh is connected to the cathode as a counter electrode, and is placed in a corrosion tank containing a polishing liquid and subjected to electrochemical post-treatment.

2. The method for removing support and finishing inner wall of complex inner cavity structure by laser additive manufacturing according to claim 1, characterized in that: In step S1, the aluminum alloy includes any one of Al-Cu alloy, Al-Mg-Si alloy, Al-Zn alloy, trace element modified Al-Mg alloy, and trace element modified Al-Mn alloy.

3. The method for removing support and finishing inner wall of complex inner cavity structure by laser additive manufacturing according to claim 2, characterized in that: The trace element is any one of Sc, Zr, Er and Ti or a combination of two or more thereof.

4. The method for removing support and finishing inner wall of complex inner cavity structure by laser additive manufacturing according to claim 1, characterized in that: In step S1, the nickel-based alloy includes any one of GH4169 alloy, Inconel 600 alloy, Inconel 625 alloy, Rene 80 alloy, Rene 125 alloy, and Rene 142 alloy.

5. The method for removing support and finishing inner wall of complex inner cavity structure by laser additive manufacturing according to claim 1, characterized in that: In step S2, the overhanging surface is identified according to the base alloy, wherein the angle between the aluminum alloy and the substrate is ≤45°, and the angle between the nickel-based alloy and the substrate is ≤35°. Self-use supports are added to the marked overhanging surface, and the support types include any one of block supports, conical supports, and mixed supports.

6. The method for removing support and finishing inner wall of complex inner cavity structure by laser additive manufacturing according to claim 1, characterized in that: In step S2, the bottom boundary of the "solid material area" coincides with the model contour; the thickness of the "weakened interface area" is between 0.5 mm and 1 mm, and its top interface coincides with the model contour; the top area of ​​the "support structure area" coincides with the bottom of the "weakened interface area".

7. The method for removing support and finishing inner wall of complex inner cavity structure by laser additive manufacturing according to claim 1, characterized in that: In step S3, the laser energy density of each interface characteristic area is calculated by the formula η = P / V D is determined; where the laser power is defined as P , unit W; the laser scanning speed is defined as V , unit: mm / s; scanning distance is defined as h , unit μm; scanning layer thickness is defined as d, Unit: μm.

8. The method for removing support and finishing inner wall of complex inner cavity structure by laser additive manufacturing according to claim 7, characterized in that: Laser power P The value range is 200-150 W, and the laser scanning speed V The value range is 800 mm / s-2500 mm / s, and the scanning interval is h The value range of is 60-120μm, and the value range of scanning layer thickness is 30-50μm.

9. The method for removing support and finishing inner wall of complex inner cavity structure by laser additive manufacturing according to claim 1, characterized in that: When the matrix material is aluminum alloy, the electrolyte is: Na2CO3 80-120g / L, Na3PO4 45-75g / L, NaOH15-40g / L, complexing agent 15-40mL / L, solvent is water; bath temperature 50-80℃, current density 5-20A / dm 2 , voltage 2-4V, time 15 min -4 h.

10. The method for removing support and finishing inner wall of complex inner cavity structure by laser additive manufacturing according to claim 1, characterized in that: In step S4, when the matrix material is a nickel-based alloy, the electrolyte is a mixed aqueous solution of 60-80% phosphoric acid and 20-40% sulfuric acid, the bath temperature is 40-70°C, and the current density is 40-60A / dm 2 , voltage 2-4 V, time 1 min -30 min.

Citation Information

Patent Citations

  • Method for preparing suspension structure by compounding metal three-dimensional forming heterogeneous support and chemical milling

    CN111390169A

  • Flame tube manufacturing method based on laser powder bed melting additive manufacturing technology

    CN115475958A

  • Self-removing method for 3D printing rare earth modified high-strength aluminum alloy constraint structure

    CN115625346A

  • Titanium-aluminum heterogeneous material laser additive manufacturing method based on interface gradient technology

    CN117340272A

  • Process controlled dissolvable supports in 3D printing of metal or ceramic components

    US20190039137A1